Foot care among male diabetics in family practice center, Abha, Saudi Arabia - Yahia M Al-Khaldi (Wolters Kluwer Medknow Publications, 2008)
Objective: This study aims to assess the behaviors of diabetic males towards their foot care at Al-Manhal Center of Family Practice, Aseer Region, KSA. Methodology: A cross-sectional study was conducted for male diabetics in the Aseer region, KSA, during the first quarter of the year 2004.A questionnaire and physical examination of the foot were used to assess their behaviors towards foot care. Results: All the male diabetic patients (107) who attended during the study period were assessed. Mean age was 58 years, mean duration of DM was 10 years. Good diabetic control was 24%, 37% did not know the negative effect of DM on the feet,9-22% had different symptoms of diabetic foot ,53% checked their feet regularly ,31% had fungal infection while an absence of pulse was detected in 7%. Conclusion: This study revealed that many diabetics had negative behaviors towards foot care. There is a need for intensive health education and regular assessment in order to detect ,prevent and manage diabetic foot as early as possible.